If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2) + -3b = 72 Multiply 6 * 2 12 + -3b = 72 Solving 12 + -3b = 72 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -3b = 72 + -12 Combine like terms: 12 + -12 = 0 0 + -3b = 72 + -12 -3b = 72 + -12 Combine like terms: 72 + -12 = 60 -3b = 60 Divide each side by '-3'. b = -20 Simplifying b = -20
| 40+7x=5-14x | | 2x^4+2y^4=4xy-1 | | 14x+15=3(8x-15) | | 2(x-12)+13=4x+17 | | 5(x+4)=6(x-6) | | 55x-5y=5.7 | | 100m^8+9= | | 50*1+5+5*10-10= | | 6r+5d-5r= | | (x-8)-(x+6)=9x | | 5/13=y | | 3/5x-78 | | 4x+23=-33 | | 5x+11=4x+4 | | 7(7x-2)=27+8x | | -69+7x=93+x | | -5x-20=-8x+28 | | 4(3x+1)=5x+25 | | 3x+20=2d+40 | | -75+9x=40+4x | | 2x-8=6x+10 | | 35+7x=-7(4-4x) | | -x-17=-3x+9 | | 5n^2-80=-30n | | -53+12x=73+3x | | 35+7a=6(1+6a) | | -2x-5x-4+2x+12=x | | 6x-113=2x-5 | | 3(m+1)-2m=o | | 7x+10=5*(3+x) | | (x+2)(x-7)=18 | | 2y-3(y+1)=(5y+3)+5 |